Dissertation Proposal
The dissertation proposal is foundational to the dissertation manuscript. Its purpose is to describe the research idea, critically explore the multiple perspectives in the literature, and present a discussion on the appropriate methodology to conduct the inquiry. In proposing a dissertation study, the proposal demonstrates that the student has a command of both the topic area and the methodologies needed to conduct the research. The proposal should follow the most recent version of the CSUCI Format and Evaluation Guidelines for Dissertation Preparation.